STUDIES ON THE BIOLOGY OF BULINUS TRUNCATUS UNDER LABORATORY CONDITIONS - F. Arfaa; GH. Sahba; J. Massoud (Tehran University of Medical Sciences, 1976)
A two-year laboratory study on the biology (including self-fertilization) of Bulinus truncatus, the intermediate host of Schistosoma haematobium, S. bovis and Paramphistomum microbotrium in Iran, has revealed information on the longevity, reproduction, hatchability rate, hatching time during various months of the year, and growth and mortality rates of this snail. It was found that the reproduction, hatchability and growth rate of Bulinus truncatus increase under condition of self-fertilization.